Unravelling the dilemma of self-medication in Egypt: a cross-sectional survey on knowledge, attitude, and practice of the general Egyptian population - Hossam Tharwat Ali; Mostafa Barakat; Ahmed Reda Abdelhalim; Ibrahim Noureddin Al-Kurd; Muhammad Kamal-Eldeen Muhammad; Mohamed Mostafa Sharkawy; Mohamed Elbahnasawy; Samar Ahmed Amer; Self-Medication Collaborative Group (BMC, 2024)
Abstract Background Self-medication (SM) is a rising public health issue, especially in developing countries. It can be associated with various problems such as the delayed seeking of medical advice, drug interactions, and serious events such as antimicrobial drug resistance. We aimed to evaluate the Egyptian general population's knowledge, attitudes, and practices of SM. Methods We employed a cross-sectional design between February 7th and March 8th, 2023 using a self-administered questionnaire available in Arabic. The questionnaire was developed based on previous studies and included four domains: sociodemographic data, knowledge, attitude, and practice of SM. We utilized both online (Google Forms) and paper surveys, utilizing convenience and snowball sampling methods. Data were analyzed using R Statistical Software (v4.1.3; R Core Team 2022). Results 1630 Egyptian individuals (838 females and 792 males) from the seven provinces were enrolled, with a median age of 25 years (IQR: 22-40). Around 55.97% and 48.28% of the participants had good knowledge and favorable attitudes regarding SM respectively, while 62.8% had practiced SM in the previous three months. The most frequently used medications were painkillers (60.74%) followed by antibiotics (32.13%) and antipyretics (28.61%). The pharmacist's recommendation was the source of SM for 53.61% while 31.53% used old medications at home. Most participants (59.08%) practiced SM because they thought they had simple or minor symptoms. The multivariate regression analysis revealed that females had significantly higher knowledge of SM than males (aOR: 2.10; 95%CI: 1.64-2.71; p-value < 0.001), with no significant differences in practice (aOR: 1.24; 95%CI: 0.99 - 1.56; p-value = 0.065). Individuals working or studying in the medical field were significantly more knowledgeable about SM (aOR: 4.30; 95%CI: 3.27-5.69; p-value < 0.001) and more likely to practice SM (aOR: 1.65; 95%CI: 1.26-2.17; p-value < 0.001). The odds of SM decreased with favorable attitudes (aOR: 0.44; 95%CI: 0.36-0.55; p-value < 0.001) while surprisingly, knowledge level was not significantly contributing to SM practice (aOR: 1.15; 95%CI: 0.90-1.48; p-value = 0.268). Conclusions SM is prevalent in Egypt, highlighting the importance of raising awareness and encouraging physician consultation as a priority. Governments, healthcare organizations, and educational institutions need to collaborate to provide the necessary support and resources.